The Influence of Giving Yacolt on The Innovative Production of Black Soldier Fly-BSF (Hermetia Ilucens) - Leopoldino V. Martins; Alexander B. Serra; Murlita (Jurnal Cakrawala Akademika, 2025)
The objective of this study is to find out the effect of giving Yacolt on the innovative production of BSF flies and to find out which Yacolt is better for BSF fly production The method of this research uses the Complete Experimental Design (CED), with its 4 treatments and 3 repetitions, a total of 36 experimental units as the following combination: Y0 = Control (0 ML), Y1 = Yakult (50 ML), Y2 = Yakult (100 ML) and Y3 = Yakult (200 ML).The results of the study showed that the provision of Yacolt with a concentration of 100 ml had a very significant effect on all treatments. the number of BSF fly eggs with treatment Y2: 10.43a had an effect on treatment Y0, 10.43a, Y1: 10.03ab Y3: 9.43bc and Y0: 9.13c. from the results of the study showed that the provision of yakult with a concentration of 100 ml had a very significant effect on all treatments. the number of changes in fly eggs to BSF larvae with treatment Y2: 10.43a had an effect on treatment Y2: 318.33 a, Y1: 200.67 b, Y3: 110.33 c and Y0: 29.00 d and from the results of the study showed that the provision of yakult with a concentration of 100 ml had a very significant effect on all treatments. the number of BSF Magots with treatment Y2 336.33 a had an effect on treatment Y2: 336.33 a, Y1: 204.00 b, Y3: 95.67 c and Y0: 19.33 d.